1995
DOI: 10.1007/bf02246266
|View full text |Cite
|
Sign up to set email alerts
|

Euphorigenic doses of cocaine reduce [123I]β-CIT SPECT measures of dopamine transporter availability in human cocaine addicts

Abstract: The in vivo potency of euphorigenic doses of intravenous cocaine for displacing [123I]beta-CIT ([123I]2 beta-carbomethoxy-3 beta-(4-iodophenyl)tropane) binding to striatal dopamine transporters (DAT) was assessed in human cocaine addicts using single photon emission computed tomography (SPECT). Cocaine-dependent subjects (n = 6) were injected with [123I]beta-CIT and imaged 24 h later under equilibrium conditions. Sequential cocaine infusions (0.28 +/- 0.03 and 0.56 +/- 0.07 mg/kg) produced significant (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
2
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 16 publications
1
26
2
1
Order By: Relevance
“…123 I]RTI-55 as the DAT radioligand suggested that a pharmacologically active dose of cocaine, injected after the radiotracer has reached a constant level in striatum and occipital cortex, occupied only 6% of the transporters [Malison et al, 1995]. Similar experiments in mice also indicated low occupancy of the DAT by cocaine when [ 123 I]RTI-55 was used to probe unoccupied DAT .…”
Section: Transportersmentioning
confidence: 90%
“…123 I]RTI-55 as the DAT radioligand suggested that a pharmacologically active dose of cocaine, injected after the radiotracer has reached a constant level in striatum and occipital cortex, occupied only 6% of the transporters [Malison et al, 1995]. Similar experiments in mice also indicated low occupancy of the DAT by cocaine when [ 123 I]RTI-55 was used to probe unoccupied DAT .…”
Section: Transportersmentioning
confidence: 90%
“…The neuroanatomical correlates of these stimulant euphorigenic mechanisms in the dopaminergic reward regions of the human brain is very important because it might provide new avenues for potential treatments (23). Despite this, we are aware of only one study that tried to correlate cocaineinduced euphoria with changes in dopamine concentration in human subjects (24).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroreceptor imaging methods, such as positron emission tomography (PET) and single photon emission computed tomography (SPECT), permit the pharmacokinetics and receptor occupancy of drugs to be studied in clinical populations (Farde et al 1992;Volkow et al 1992;Malison et al 1995a). The application of such techniques to the measurement of mazindol's in vivo potency for DAT binding would help to inform medication development strategies aimed at treating cocaine abuse by DAT antagonism (Rothman 1990).…”
Section: Introductionmentioning
confidence: 99%